(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article, based on an analytical review of scientific sources on the problem of children’s leadership, defines the leadership abilities of an older preschooler as an integrative dynamic personal education developing in the joint activity of a child with peers under the guidance of adults, the structure of which is formed by the unity of cognitive, emotional-volitional, activity-creative and evaluative-reflective components. A structural model of a preschooler’s leadership abilities is also presented.